Microtubule nucleation by the isolated microtubule-organizing centre of Physarum polycephalum myxamoebae. - Roobol, A; Havercroft, J; Gull, K (1982)
The nucleus--centrosome complex from Physarum polycephalum myxamoebae has been purified. The complex contained the centriole pair and pericentriolar material in association with the nucleus. Apart from some unusually stable microtubules, which appeared to be involved in maintaining the nucleus-centrosome association, endogenous microtubule arrays had been stripped from the complex during isolation. When the nucleus--centrosome complex was incubated with purified brain or myxamoebal tubulins the growth of 45-70 microtubules was initiated onto the pericentriolar material. The number and length of the nucleated microtubules was proportional to the tubulin concentration. Pretreatment of the nucleus--centrosome complex with DNase 1, RNase A, antitubulin antibody and anticentriolar antibody did not affect pericentriolar nucleation capacity, although pretreatment with DNase 1 did expose perinuclear nucleation sites that had a much lower minimal tubulin concentration for assembly than the pericentriolar site. After pretreatment with trypsin pericentriolar material and nucleation were destroyed, and microtubule elongation occurred directly onto the centriole microtubules.